2023
DOI: 10.2337/db22-0515
|View full text |Cite
|
Sign up to set email alerts
|

Topically Administered NOX4 Inhibitor, GLX7013114, Is Efficacious in Treating the Early Pathological Events of Diabetic Retinopathy

Abstract: NADPH oxidases (NOX) are major players in generating reactive oxygen species (ROS), implicated in various neurodegenerative ocular pathologies. The aim of this study was to investigate the role of NOX4 inhibitor (GLX7013114), in two in vivo experimental streptozotocin (STZ) paradigms depicting the early events of diabetic retinopathy (DR). Diabetic-treated animals received GLX7013114 topically (20μl/eye, 10mg/ml, once daily), for 14d (Paradigm A/preventive) and 7d (Paradigm B/treated), 48hr and four wks post S… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 46 publications
3
14
0
Order By: Relevance
“…The expression of NOX1, NOX2, and NOX4 isoforms of NADPH oxidases has been identified in different types of retinal cells, including macro- and microglia, pericytes, and endothelial cells [ 6 , 7 ], as well as retinal neurons [ 59 ]. Our studies are in agreement with other investigations reporting an increased expression of NOX2 in animal models of DR [ 60 , 61 ], as well as an increased expression of other NOX isoforms [ 9 , 11 , 62 ]. ROS derived from the NOX2 isoform are significantly increased in ESDR, causing mitochondrial damage and further induction of oxidative stress [ 61 ].…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…The expression of NOX1, NOX2, and NOX4 isoforms of NADPH oxidases has been identified in different types of retinal cells, including macro- and microglia, pericytes, and endothelial cells [ 6 , 7 ], as well as retinal neurons [ 59 ]. Our studies are in agreement with other investigations reporting an increased expression of NOX2 in animal models of DR [ 60 , 61 ], as well as an increased expression of other NOX isoforms [ 9 , 11 , 62 ]. ROS derived from the NOX2 isoform are significantly increased in ESDR, causing mitochondrial damage and further induction of oxidative stress [ 61 ].…”
Section: Discussionsupporting
confidence: 93%
“…We have previously shown that inhibition of all NOX isoforms (pan-NOX inhibitor, VAS2870) or specific NOX1 inhibition (ML171) reduced the AMPA-induced loss of NOS-expressing amacrine cells when co-administered with AMPA. In contrast, the NOX4-specific inhibitor (GLX7013114), had no effect [ 11 ]. These results suggest that NADPH oxidases are implicated in the AMPA-induced neurodegenerative changes in the retina with NOX isoforms displaying differential roles.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Given the pivotal role of NADPH oxidases [ 9 , 36 ], in particular Nox4 [ 3 , 18 ], in ROS generation in retinal ECs, understanding how Nox4 upregulation and increased ROS mediate diabetes-induced vascular damage [ 37 , 38 ] would have high translational significance. Indeed, a recent study demonstrates that topical administration of a Nox4 inhibitor successfully reduced retinal inflammation, neurodegeneration, and vascular leakage [ 39 ]. Future investigation to elucidate the role of Nox4 in the regulation of endothelial tight junction proteins, such as claudin-5, could provide important insight into the mechanisms of Nox4 inhibition on protecting retinal vessels in DR.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies indicate that several anti-inflammatory therapies ameliorate the pathogenesis of diabetic retinopathy in diabetic models in vivo and in vitro, including IMD-0354, a specific NF-κB blocker [95], GSK-872, specific necroptosis inhibitor [96], hsa_circ_0000047 which targets miR-6720-5p/CYB5R2 axis [97], topical administrated NADPH oxidases 4 inhibitor, GLX7013114 [98], a non-steroid mineralocorticoid receptor, finerenone [99], and miRNA-124 [100]. Although there are a variety of diabetic models, including rodents and Drosophila, which are available worldwide, no ideal models of diabetic retinopathy have been established yet [101,102].…”
Section: Therapeutic Options Of Anti-inflammation For Diabetic Retino...mentioning
confidence: 99%